Pemetaan Risiko Produksi Pada Usahatani Padi Sawah di Desa Labulu-Bulu Kecamatan Parigi Kabupaten Muna - Nurhidayah, Nurhidayah; Rianse, Usman; Abdullah, Weka Gusmiarty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
The study of this research was to mapp the risks of rice production in Labulu-Bulu Village, Parigi District, Muna Rigency. This research was conducted in November 2016 until Juny 2017. Act of sample in did with simple random sampling the number population 38 of farmers. Date analysis was used qualitative and quantitative descriptive. The results showed mapping of risk in rice production, namely (a) operational risk with high-risk level was using of fertilizers, using of pesticides and nominal income; moderate risk level was production quantity; and low-risk level was provide seeds, provide fertilizers, provide pesticides, rent tools and machinery andÂ  growth of seeds; (b) Human resource risk with high-risk level was renting labor recruitment and providing planting labor; moderate-risk level was safety of labor in preparation and management of land, safety of labor in plants maintenance, provide of labor in harvest;Â  low-risk level was using of family labor, and safety of labor I plant growth;. (c) Technology risk with high-risk level was using of tools and machinery, damage tools and machinery in harvest and harvest method; moderate-risk level was planting methods and fertilizing methods; and low-risk level was opening land methods processing of land methods; (d) externality risk with high-risk level was disrupted in grain drying; moderate-risk level was weather in oppening and management of land and pests in post-harvest; and low-risk level was exposure to weather condition when maintenance, pests and desease on seedling.